Tef as a case for investment in orphan crop breeding and seed systems development - Tadele, Zerihun; Renou, Camille; Chanyalew, Solomon; Johnson-Chadwick, Victoria; Osure, George; Robinson, Mike; Barker, Ian; Klauser, Dominik (Frontiers in Plant Science, 2024)
Orphan crops are crops that are of substantial importance to food security and economic growth at a local or regional scale, yet lacking investment in crop improvement and seed systems development.Tef is an example of such an orphan crop. It is vital to economy and food systems in the Horn of Africa, yet investment in breeding and agronomy is very limited. Since almost 20 years, the Syngenta Foundation for Sustainable Agriculture has invested in tef, supporting work to both develop and disseminate improved varieties to farmers in Ethiopia. To date, this has led to the release of four improved varieties. As the project also invested in the development of seed systems for improved tef varieties, it allowed us to monitor seed production and variety adoption over time. The data obtained from seed production monitoring over 7 years and 4 varieties from both formal and informal seed systems shows a total of 1227 tons of tef seed from improved varieties delivered to farmers in Ethiopia. Assuming an average genetic gain of 0.4 tons per hectare, this suggests that the value generated to farmers and local value chains from tef breeding and seed systems development exceeds the investment by an order of at least 2.5. With this paper, we want to make an investment case for more long-term investment breeding and seed systems development and stimulate replication of the approach to other orphan crops. We further want to call for a continued investment in tef crop improvement and seed systems development.